Rekonfigurasi Otoritas Hukum Islam di Era Media Sosial: Antara Ijtihad Institusional dan Otoritas Algoritmik - Upi Sopiah Ahmad; Nurhayati; Azhari Akmal Tarigan; Mhd Nur Husein Daulay (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The development of social media has transformed the relationship between Muslim communities and Islamic legal authority, shifting from a centralized model centered on ulama and fatwa institutions toward an algorithm-based digital ecosystem. This study analyzes the reconfiguration of Islamic legal authority through the interaction between institutional ijtihad and algorithmic authority, as well as its implications for legal and social-cultural change. Employing normative legal research with a conceptual approach and socio-legal perspective, data were obtained through literature review and analyzed qualitatively using content analysis. The findings indicate that social media has driven a shift in the legitimacy structure of fatwas, which no longer depend solely on scholarly chains of transmission (sanad) but also on digital visibility shaped by algorithms. The relationship between the two is co-existential and complementary ijtihad serves as the normative source, while algorithms determine the reach and social acceptance of fatwas. From a socio-legal perspective, this transformation implies the pluralization of authority sources, increased public participation, and the growing influence of digital technology in shaping trust in Islamic law. This study offers the concept of platform-mediated religious authority as a model explaining that contemporary Islamic legal authority is formed through the interaction of normative legitimacy, platform-based digital distribution, and user participation in the digital public sphere